2022
DOI: 10.1589/jpts.34.140
|View full text |Cite
|
Sign up to set email alerts
|

Gait cycle time variability in patients with knee osteoarthritis and its possible associating factors

Abstract: [Purpose] Knee osteoarthritis can alter gait variability; however, few studies have investigated the associating factors with gait cycle time variability. The first objective was to compare gait cycle variability between female patients with knee osteoarthritis and healthy elderly females and to determine gait characteristics in patients with knee osteoarthritis. The second objective was to identify the associating factors with gait cycle time variability. [Participants and Methods] The participants included 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Only a little amount of study has been done to determine the relationship between muscle activation patterns, especially the moment of the vastus lateralis, medial gastrocnemius, and rectus femoris in connection to the knee OA development. Patient with knee osteoarthritis was reported has a slow walking speed compared to normal individual (Akimoto et al, 2022). Walking speed also has become one of the important predictors of outcome for knee OA intervention (Harkey, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Only a little amount of study has been done to determine the relationship between muscle activation patterns, especially the moment of the vastus lateralis, medial gastrocnemius, and rectus femoris in connection to the knee OA development. Patient with knee osteoarthritis was reported has a slow walking speed compared to normal individual (Akimoto et al, 2022). Walking speed also has become one of the important predictors of outcome for knee OA intervention (Harkey, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Static plantar pressure analysis is widely used in the study of patients' balance function [10]. Previous studies have reported abnormal balance function in patients with KOA, which is characterized as a great amount of swing on the center of gravity in the left and right directions during one-leg stance and impaired postural control [8,9,11]. In the present study, the static plantar pressure of unilateral KOA patients tended to be distributed on the unaffected side, which is caused by a compensatory behavior of trunk lateral flexion to alleviate pain on the knee [5,12], manifested as pelvic rotation and reduction of weight bearing on the affected side.…”
Section: Discussionmentioning
confidence: 99%
“…Gait variability is an indicator that can quantify to postural stability and showed to be predict to faller based on lack of balance ability when compared with gait speed and functional status by a previous study [ 12 ]. Moreover, the high gait variability was reported in patients with knee OA with an impaired functional ability [ 13 ] and was correlated with a poor clinical score [ 14 ] and fear of falling [ 15 ]. Then, the gait variability may serve as a potential indicator to assess ambulatory function in knee OA.…”
Section: Introductionmentioning
confidence: 99%